2002
DOI: 10.1124/jpet.302.1.232
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Treatment Induced Peroxisome Proliferator-Activated Receptor α Expression and Decreased Plasma Nonesterified Fatty Acids and Liver Triglyceride in Fructose-Fed Rats

Abstract: We aimed to investigate the effect of atorvastatin (5 and 30 mg/kg/day for 2 weeks) on hepatic lipid metabolism in a well established model of dietary hypertriglyceridemia, the fructosefed rat. Fructose feeding (10% fructose in drinking water for 2 weeks) induced hepatic lipogenesis and reduced peroxisome proliferator-activated receptor ␣ (PPAR␣) expression and fatty acid oxidation. As a result, plasma and liver triglyceride and plasma apolipoprotein B (apoB) levels were increased. Atorvastatin, 5 and 30 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
99
1
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 128 publications
(122 citation statements)
references
References 42 publications
15
99
1
7
Order By: Relevance
“…Although we did not measure the mechanics of fatty acid circulation in the present study, the circulating level of plasma FFA depends on the lipolysis of circulating lipoproteins, the rate of FFA release from adipose tissue, and the rate at which these fatty acids are taken up and reesterified by tissues (52). According to the fatty acid stealing hypothesis (53), PPARγ may act to promote the movement of FFA into skeletal muscle and other tissues having a high level of PPARγ (54).…”
Section: Fig 3 Comparison Of Pparγ Expression In Skeletal Muscles mentioning
confidence: 84%
“…Although we did not measure the mechanics of fatty acid circulation in the present study, the circulating level of plasma FFA depends on the lipolysis of circulating lipoproteins, the rate of FFA release from adipose tissue, and the rate at which these fatty acids are taken up and reesterified by tissues (52). According to the fatty acid stealing hypothesis (53), PPARγ may act to promote the movement of FFA into skeletal muscle and other tissues having a high level of PPARγ (54).…”
Section: Fig 3 Comparison Of Pparγ Expression In Skeletal Muscles mentioning
confidence: 84%
“…34,35 Several studies have shown that statins increase PPARa expression in vitro and in vivo and induce transcriptional activity. [36][37][38] Limiting the development of drug resistance in the era of directly acting antiviral therapies will be critical. This will likely involve synergy with other compounds demonstrating antiviral activity.…”
Section: Discussionmentioning
confidence: 99%
“…The relative levels of specific messenger RNAs (mRNAs) were assessed by reversetranscription polymerase chain reaction, as described. 13 Adenosyl phosphoribosyl transferase was used as an internal control. The number of cycles, primer sequences, and resulting polymerase chain reaction products are listed in Table 1.…”
Section: Rna Preparation and Analysismentioning
confidence: 99%